When I grow up I'll be an engineer - Miller, Connie Colwell, 1976-; Baroncelli, Silvia (Mankato, MN : Amicus Illustrated/Amicus Ink, 2019)
Readers follow along with a civil engineer as a young girl pretends to be an engineer designing and building a bridge with her father. Includes a glossary of engineering terms and an activity that lets readers practice building skills.
3.4
K-3
600L
Keywords: Civil engineering -- Juvenile literature; Civil engineers -- Juvenile literature; Civil engineering; Civil engineers; Vocational guidance; Picture books -- Juvenile literature